The Role of Extreme Weather Events in Shifting Climate Patterns in Tropical Regions - Manuel, Felipe (Global Writing Academica Researching & Publishing, 2024)
Extreme weather events, such as intense storms, prolonged droughts, and heavy rainfall, are becoming more frequent in tropical regions as a result of global climate change. This paper investigates how these events are altering long-established climate patterns in equatorial zones. By examining recent data on extreme weather trends and their impact on local climates, ecosystems, and human societies, this study highlights the critical role these events play in shaping the future of tropical climates. The research also discusses the implications for environmental sustainability and the resilience of communities living in tropical areas. Understanding the connection between extreme weather and shifting climate patterns is crucial for developing effective adaptation and mitigation strategies in these vulnerable regions.